Effectiveness of Soybean Pulp Oil as a Natural Preservative for Wagyu Beef: Impact on Moisture Retention and Nutritional Composition - Hasanah, Qomariah (ISEJ : Indonesian Science Education Journal, 2024)
The Covid-19 pandemic has rapidly transformed global education systems, pushing institutions toward online learning. This study explores the effectiveness of WhatsApp as an e-learning tool for the Biomolecules and Metabolism course in the Tadris IPA Program at IAIN Bengkulu during the pandemic. A mixed-methods approach, including a survey and semi-structured interviews, was employed to assess students' perceptions of WhatsApp's usability, its impact on engagement, and its effectiveness in facilitating learning. The findings show that WhatsApp was widely regarded as user-friendly, cost-effective, and accessible even in areas with weak internet connectivity. A majority of students (90%) reported that WhatsApp helped reduce data usage compared to other platforms, making it a more viable option for online learning. Moreover, WhatsApp’s group chat, document sharing, and audio message features significantly enhanced student engagement and participation. This study highlights the potential of WhatsApp as an alternative e-learning tool, particularly in resource-constrained environments. The novelty of this research lies in its focus on using WhatsApp in a specialized science course, contributing to the understanding of how mobile messaging platforms can support higher education in the post-pandemic era. The results suggest that WhatsApp can be a valuable tool for improving learning outcomes in science courses, though further research is needed to address challenges related to information overload and synchronous learning limitations.